Elaboración de un manual de funcionamiento, mantenimiento y plan de renovación del microscopio, centrifuga y contaje de colonias para los laboratorios de la carrera de medicina veterinaria de la Universidad Técnica de Cotopaxi - Quintana Páramo, Alejandro Patricio (2015)
At research study a manual was made to describe considered aspects most important for regarding the operation, maintenance and renewal plan of the equipment: Microscope Centrifuge and Colony Counter. Inside manual was made a maintenance plan of the equipment: optical microscope, centrifuge and colony counter by collecting data, which is a basic tool to support the development of practical lab inside of Veterinary Medicine career that determines the operation of the equipment with the respective steps to follow and help us to observe the correct functioning of the equipment and also it gives us a renewal plan which will extend the useful life of equipment, the same that is used in the departments of Histology, Microbiology, Parasitology, Anatomy, Bacteriology etc....